Container characteristics and density of Aedes aegypti larvae: a field trial of Ziziphus mauritiana leaf extract - Amaliyah, Nurul; Fathmawati, Fathmawati; Yulia, Yulia; Hikmah, Kholisotul (International Journal of Public Health Science (IJPHS), 2023)
The application of larvicide from botanical origin was extensively studied as an essential part of mosquito prevention. This study aimed to assess the difference in container index (CI) based on the characteristics of water containers using Ziziphus mauritiana leaf extract solution. A quasi- experiment research was done among 300 selected containers with temephos as a control and 9% of Ziziphus mauritiana leaf extract solution as a treatment. The types of containers observed in this study were the type of water, container materials, location, container lids, and community behavior regarding immature Aedes aegypti breeding eradication. Water containers without lids and outside the house had a significantly higher CI among treatment (OR=26; 3.69–18.34; p=0.001 and OR=20; 2.04–19.64; p=0.003) and control group (OR= 10.83; 95% CI=1.96–59.83; p=0.005 and OR=6.43; 95% CI=1.02–40.26; p=0.04). Negative community behavior regarding the prevention and eradication of Aedes immatures was significantly associated with greater odds of high CI among treatment and control, with OR=37.5; 3.64–38.65; p=0.001 and OR=16.88; 2.56-11.4; p=0.002, respectively. Furthermore, containers with rainwater out of the treatment group had a higher presence of Aedes larvae (OR=11.25; 1.15–11.05; p=0.03).